PERANAN APARATUR DESA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT TERHADAP PEMBANGUNAN DI DESA SETIA JAYA KECAMATAN TERIAK KABUPATEN BENGKAYANG - Leonardus Wendi E.42009048 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2017)
This study aims to describe and analyze the role of government officials in the village increased community participation in Setia Jaya village Teriak subdistrict, Bengkayang Regency. The title of this thesis concerns raised by the village government's role is less active in increasing public participation in the development. This study used a qualitative approach and descriptive research. Collecting data using observation, interview and documentation. Then in analyzing the data using data reduction, data display, and conclusion. These results indicate the role of both the village government as a facilitator, motivator and mobilizer considered less active in moving and improving public participation in the development. Keywords: Participation , Rural Development , Society and Government .